Possibilities and Prospects of Modification of the Intestinal Microbiome - E. G. Malaeva; I. O. Stoma (SINAPS LLC, 2022)
The gut microbiome is a variable system that not only adapts to signals and information coming from humans, but also affects its host due to a complex system of interactions of living microorganisms, phages, viruses, plasmids, mobile genetic elements, molecules synthesized by microorganisms, including their structural elements (nucleic acids, proteins, lipids, polysaccharides), metabolites (signaling molecules, toxins, organic and inorganic molecules) and molecules synthesized by the human body. Modification or modulation of the microbiome by correcting the diet, the intensity of physical activity, the appointment of components of personalized products (prebiotics, probiotics, paraprobiotics, postbiotics, autoprobiotics) can lead to changes in species diversity, the metabolic profile of the intestinal microbiome and the regulation of metabolic processes, local and systemic response to infectious diseases, drug metabolism, the activity of many organs and systems due to the presence of physiological axes "gut microbiome-central nervous system", "gut microbiome-liver", "gut microbiome-kidneys" and some others. New, targeted directions of modification of the intestinal microbiome are being studied, which consist in targeted exposure to pathogenic microorganisms, including intracellular and resistant to antibacterial drugs.The dynamic nature of the intestinal microbiome, the ability to change and adapt under the influence of some of the studied factors opens up new promising areas of medical prevention and treatment of somatic and mental diseases. Undoubtedly, the modification of the microbiome for clinical purposes is aimed at improving human health. However, individual, not always predictable, changes in the microbiome in response to modifying factors may be due to the uniqueness of the species composition and functional potential of microorganisms in each person.